Transformation of Education Curriculum Development in Indonesia: History, Challenges, and Future Opportunities - Muhammad Dzunniam; Raikhan Raikhan (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2025)
The development of the education curriculum in Indonesia reflects the social, political, and cultural dynamics since independence. Various curriculum changes, from the 1947 Curriculum to the Merdeka Curriculum, show the government's efforts to adapt education to the needs of society and global challenges. Each change is caused by challenges, such as gaps in educational infrastructure, teacher readiness in implementation, and differences in local characteristics. In addition, factors such as political dynamics, technological changes, and job market needs play a major role in the evolution of synchronization. Despite facing many challenges, great opportunities for curriculum development are open, especially with the use of digital technology, strengthening global literacy, and collaboration with world industries. The Indonesian government has taken strategic steps to design a curriculum that is adaptive to global changes, including the development of data-based policies, teacher training, and cooperation with international institutions.